ON LEGAL PROTECTION OF COMMERCIAL SECRET IN THE CONTEXT OF IMPROVING THE EFFECTIVE LEGISLATION - Beluga, Yulia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to research the problems of legal protection of commercial secret by the norms of the effective legislation. Research methods: the research was made using the generally accepted methods of scientific cognition, such as: analytical, comparative and legal, systematic and structural, formal and logical methods, method of law interpretation, etc. Results: an author researched the commercial secret concept under the legislation of Ukraine, defined the commercial secret main features analysing the national legislation and doctrinal points of view of scientists, analysed the judicial practice, legislative acts of Ukraine and defined the problematic aspects of commercial secret legal protection. Discussion: in the article an author searches the ways to solve the problems of commercial secret legal protection. However, in the most countries the commercial secret has proper legal protection, nowadays in Ukraine there is no effective mechanism to protect information that is considered as commercial secret. Moreover, the Draft of the Law «On Commercial Secret» has not been adopted yet in its final version. The effective legislation of Ukraine does not contain unified definition of the commercial secret concept. Thus, it is important to provide legislative guarantees to protect the proprietary rights to information with the limited access that is considered as commercial secret, to create necessary conditions for its owners to preserve and establish a liability for its disclosure.